Law Enforcement in Banking Criminal Act Involving Insiders - Ridwan Arifin (Jambe Law Journal, 2018)
The rise of news in the mass media related to burglary cases of bank customer funds further raises public awareness of the vulnerability of the banking sector used as a means (crimes through the bank) and as the target of crime against the bank. On the other hand, the awareness is intended to further convince each party that the bank in conducting its business activities must be managed and managed by parties who have integrity and good competence. The purpose of this research is to: (1) analyze and describe the implementation of the rule of law in handling banking criminal case involving insider; and (2) to know and analyze government efforts both preventive and repressive in handling banking crime cases in Indonesia, especially in cases involving insiders. The results showed that the implementation of law in handling banking crime cases in addition to using Law No. 10 of 1998 on Amendment to Law No. 7 of 1992 concerning to Banking (Banking Act), also used several provisions of article in the Criminal Code (KUHP) and Law No. 20 Year 2011 jo. Law No. 31 Year 1999 on the Eradication of Corruption. The role of Bank Indonesia in the enforcement of law in the form of investigation and/or forensic examination of banking crime that occurred in a bank which then the result of investigation is reported to law enforcement in accordance with applicable Criminal Procedure Code. Enforcement and prevention efforts are conducted jointly through the synergy of Bank Indonesia, the Police and the Attorney. In addition, Bank Indonesia also applied the principle of know your customer and compliance function as a preventive effort for banking crime. The weakness of internal controls is the cause of the ineffectiveness of handling of banking crime cases, especially those involving insiders, a memorandum of understanding between Bank Indonesia, the Police and the Attorney Office is only a moral obligation, should be more binding so that it can become one of the more powerful law enforcement tools.